Periodontal management of gingival enlargement associated with Sturge-Weber syndrome - Sugumari Elavarasu; S Thanga Kumaran; P K Sasi Kumar (Wolters Kluwer Medknow Publications, 2013)
The Sturge-Weber syndrome is a rare uncommon neurocutaneous disorders with angiomas involving the leptomeninges (Leptomeningeal Angiomas) and skin of the face, typically in the ophthalmic (V1) and maxillary (V2) distributions of the trigeminal nerve. The cutaneous angioma is called a Port-Wine Stain. It is commonly referred to as "Sturge-Weber syndrome after Sturge and Weber who first described this affliction in 1879. This article present a case of Sturge-Weber syndrome associated with gingival enlargement, its management and follow-up results.